Level of plasma thioredoxin in male patients with manic episode at initial and post‐electroconvulsive or antipsychotic treatment. Issue 6 (14th November 2014) - Genc, Abdullah; Kalelioglu, Tevfik; Karamustafalioglu, Nesrin; Tasdemir, Akif; Gungor, Ferda Can; Genc, Esra Sena; Incir, Said; Ilnem, Cem; Emul, Murat
<x xml:space="preserve">Abstract</x> Aim Oxidative stress is defined as exposure to excessive oxidants and/or decrease in antioxidant capacity. Several studies have shown the effects of free radicals and antioxidant defense systems in bipolar disorder. We aimed to investigate the role of thioredoxin (TRX), which is a novel oxidative stress marker in patients with bipolar disorder. Methods Sixty‐eight hospitalized bipolar patients who were in manic episode were included in the study. As a control group, 30 healthy people were elected. Two groups were formed. The first group consisted of patients who were undergoing electroconvulsive treatment + antipsychotic treatment (haloperidol+quetiapine) and members of the other group were taking only antipsychotic treatment. Plasma thioredoxin levels were measured before and after treatment. Results Pretreatment plasma TRX levels of patients were significantly lower than the controls (P < 0.05). Comparing pre‐ and post‐treatment plasma TRX levels of all patients, post‐treatment plasma TRX levels were significantly lower than the pre‐treatment plasma TRX levels (P < 0.05). When we compared TRX levels between the electroconvulsive treatment + antipsychotic treatment group and the antipsychotic treatment group (P > 0.05) and within groups (P > 0.05) we did not find any statistically significant difference. Conclusion Oxidative balance is impaired in bipolar disorder manic episode in favor of the oxidants. Decreased plasma TRX levels in the manic episode probably mean that antioxidant capacity is decreased in the bipolar disorder patients in the manic episode. Further studies in euthymic and depressive states are also needed to gain more insight into the role of TRX in bipolar disorder.